Nanometer deodorization fireproof plate and production process thereof

By adding polydopamine-coated nanodeodorizing powder to the fire-resistant plate, using its catalytic degradation ability, the problem of removing hydrogen sulfide and ammonia odor in the laboratory is solved, and the air quality is significantly improved. It is suitable for animal laboratories, etc. place.

CN119263767APending Publication Date: 2025-01-07NANJING HEADWAY FURNITURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310375.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In animal laboratories, when ventilation is poor, hydrogen sulfide and ammonia odor gases produced by the excrement of experimental animals affect the air quality and pose a threat to the health of the experimenter. The existing fire-proof boards lack effective deodorization functions.

Method used

Add deodorizing filler to the fire-proof board, and make slurry by magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, alumina powder, hydroxymethyl cellulose, sawdust, fly ash and aluminum silicate fibers. Polydopamine-coated nanodeodorizing powder is added to the molding process to utilize its ability to catalyze the degradation of odor molecules.

Benefits of technology

The catalytic degradation effect of hydrogen sulfide and ammonia has been achieved, and the air quality has been significantly improved. It is suitable for animal laboratories and other places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050490740000071
    Figure BDA0005050490740000071
Patent Text Reader

Abstract

The invention discloses a nanometer deodorization fireproof board and a production process thereof, and belongs to the technical field of fireproof boards, magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, alumina powder, hydroxymethyl cellulose and clear water are added into a stirring kettle to be mixed uniformly, then saw dust, fly ash and aluminum silicate fibers are added into the stirring kettle to be stirred uniformly, and a mixture is obtained; the preparation method comprises the following steps: uniformly mixing the raw materials to obtain slurry, carrying out mold pressing on the slurry to obtain a prefabricated plate, uniformly stirring and mixing a deodorization filler, toner and melamine resin to obtain resin slurry, dipping the prefabricated plate in the resin slurry, carrying out mold pressing, and demolding to obtain the nano deodorization fireproof plate. The nano deodorization powder takes a silicon oxide porous carrier as a matrix, has a larger specific surface area and is beneficial to loading more MOF products obtained by reaction of copper nitrate hydrate and 2-methylimidazole, copper ions in the nano deodorization powder provide a large number of active centers and promote degradation of odor molecules, and the nano deodorization powder has a catalytic degradation effect on hydrogen sulfide and ammonia gas; the method has application prospects in animal laboratories and other places.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fireproof panels, and in particular relates to a nano deodorizing fireproof panel and a production process thereof. Background Art

[0002] Fireproof board is also called fire-resistant board. It is made of base paper through the process of impregnation of melamine and phenolic resin under high temperature and high pressure. The specific manufacturing process includes the impregnation, drying and cutting of decorative paper and kraft paper, and then stacking these impregnated papers together and placing them under a press. They are continuously and evenly pressed under high temperature and high pressure for a period of time, and then trimmed, sanded, and inspected for quality.

[0003] Fireproof panels have excellent fireproof properties, can maintain a certain stability at high temperatures, are not easy to burn, and thus play a flame retardant role. This type of panel can be sawed, grinded, and nailed, which is easy to process and install. It can better meet design requirements and is widely used in interior decoration, furniture, cabinets, laboratory countertops, exterior walls, fireproof ceilings and other fields.

[0004] During the use of animal laboratories, experimental animals will produce excrement such as feces and urine. These excrement will produce smelly gases such as hydrogen sulfide and ammonia during the decomposition process. If the ventilation effect is not good, it will not only affect the air quality of the laboratory, but may also affect the health of the experimenters. It is very necessary to use panels with deodorizing function during the laboratory decoration process. Summary of the invention

[0005] The purpose of the present invention is to provide a nano deodorizing fireproof board and a production process thereof, wherein a deodorizing filler is added to the fireproof board to catalyze and degrade odorous gases.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A production process of a nano deodorizing fireproof board comprises the following steps:

[0008] Step 1: adding magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, aluminum oxide powder, hydroxymethyl cellulose and clean water into a stirring tank and mixing them evenly, then adding sawdust, fly ash and aluminum silicate fiber into the stirring tank, mixing evenly to obtain a slurry;

[0009] Step 2: pour the slurry into a mold with a non-woven fabric on the bottom, cover the non-woven fabric on the surface after casting and spreading, mold at a temperature of 170-180°C and a pressure of 4.5-5MPa for 25-30 minutes, dry and demould, and sand and polish to obtain a prefabricated board;

[0010] Step 3: Stir and mix the deodorizing filler, color powder and melamine resin evenly to obtain resin slurry, immerse the prefabricated board in the resin slurry for 5-10 minutes, transfer it to the mold, mold it at a temperature of 185-190°C and a pressure of 3-3.5MPa for 5-8 minutes, and demold it to obtain the nano deodorizing fireproof board.

[0011] Furthermore, the mass ratio of magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, aluminum oxide powder, hydroxymethyl cellulose, clean water, sawdust, fly ash and aluminum silicate fiber is 60-80:20-30:10-15:10-15:0.5-1:5-7:8-12:8-12:15-20.

[0012] Furthermore, the mass ratio of the deodorizing filler, the color powder and the melamine resin is 5-8:2-4:90-95.

[0013] Further, the deodorizing filler is prepared by the following steps:

[0014] Add Tris-HCl buffer with a pH value of 8.5 and dopamine hydrochloride into a reaction kettle, stir and mix, then add nano deodorant powder into the reaction kettle, stir at 200-300 r / min for 15-20 min, ultrasonically disperse for 5-10 min, then stir and react at 20-25° C. for 12-14 h, centrifuge and filter, and vacuum dry the filter cake to obtain a deodorant filler.

[0015] Furthermore, the usage ratio of Tris-HCl buffer, dopamine hydrochloride and nano deodorant powder is 1000mL:5g:2.2-2.4g.

[0016] Further, the nano deodorant powder is prepared by the following steps:

[0017] Step 1: Add methyl orthosilicate, polyethylene oxide and hydrochloric acid with a molar concentration of 0.01 mol / L into a reactor, stir at 300-500 r / min for 60-80 min, then add propylene oxide into the reactor and continue stirring for 1-2 min, let stand at 35-40° C. for 66-72 h, soak the formed gel in anhydrous ethanol for 5-6 h, wash it 2-3 times, vacuum dry it, and crush it to obtain a porous carrier powder;

[0018] Step 2: Add hydrated copper nitrate, 2-methylimidazole and anhydrous methanol into the reactor, stir at 200-300 r / min for 60-80 min, then add the porous carrier powder into the reactor, ultrasonically disperse for 20-30 min, let stand at 35-40° C. for 24 h, centrifuge and filter, wash the filter cake with anhydrous methanol for 3-5 times, transfer to a tubular furnace after vacuum drying, and keep warm for 2.5-3 h under a protective gas atmosphere at 800-820° C. to obtain a nano deodorant powder.

[0019] Furthermore, the usage ratio of methyl orthosilicate, polyethylene oxide, 0.01 mol / L hydrochloric acid and propylene oxide is 1 mL: 0.12 g: 2.4-2.5 mL: 0.46-0.47 mL.

[0020] Furthermore, the usage ratio of hydrated copper nitrate, 2-methylimidazole, anhydrous methanol and porous carrier powder is 0.4 g: 0.84-0.85 g: 70-80 mL: 0.25 g.

[0021] Furthermore, the shielding gas is a mixture of argon and hydrogen in a volume ratio of 3:1.

[0022] Beneficial effects of the present invention:

[0023] The fireproof board of the present invention has good deodorizing effect, has catalytic degradation effect on hydrogen sulfide and ammonia, and has application prospects in places such as animal laboratories.

[0024] In the production process of the fireproof board of the present invention, the fireproof raw materials are prepared into prefabricated boards, the prefabricated boards are impregnated with resin slurry and molded, the resin slurry is added with deodorizing filler, the deodorizing filler is a nano deodorizing powder coated with polydopamine, and the polydopamine coating helps to improve the dispersion effect of the nano deodorizing powder, prevent agglomeration, and help improve the deodorizing effect. The nano deodorizing powder uses a porous silicon oxide carrier as a matrix, has a larger specific surface area, and helps to load more MOF products of the reaction of hydrated copper nitrate and 2-methylimidazole, wherein the copper ions provide a large number of active centers to promote the degradation of odor molecules. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Embodiment 1: A production process of a nano deodorizing fireproof board material, comprising the following steps:

[0027] S1: Add 100L of methyl orthosilicate, 12kg of polyethylene oxide and 240L of hydrochloric acid with a molar concentration of 0.01mol / L into a reactor, stir at 300r / min for 60min, then add 46L of propylene oxide into the reactor and continue stirring for 1min, let it stand at 35°C for 66h, soak the formed gel in anhydrous ethanol for 5h, wash it twice, vacuum dry it, and crush it to obtain a porous carrier powder.

[0028] S2: Add 4kg of hydrated copper nitrate, 8.4kg of 2-methylimidazole and 700L of anhydrous methanol into the reactor, stir at 200r / min for 60min, then add 2.5kg of porous carrier powder into the reactor, ultrasonically disperse for 20min, let stand at 35°C for 24h, centrifuge and wash the filter cake with anhydrous methanol for 3 times, transfer to a tubular furnace after vacuum drying, and keep warm for 2.5h at 800°C under a protective gas atmosphere. The protective gas is a mixture of argon and hydrogen in a volume ratio of 3:1 to obtain a nano deodorant powder.

[0029] S3: Add 1000L Tris-HCl buffer with a pH value of 8.5 and 5kg dopamine hydrochloride into the reactor, stir and mix, then add 2.2kg nano deodorant powder into the reactor, stir at 200r / min for 15min, ultrasonically disperse for 5min, then stir and react at 20°C for 12h, centrifuge and filter, and vacuum dry the filter cake to obtain a deodorant filler.

[0030] S4: Add 60kg of magnesium oxide powder, 20kg of anhydrous magnesium chloride powder, 10kg of glass fiber powder, 10kg of aluminum oxide powder, 0.5kg of hydroxymethyl cellulose and 5kg of clean water into a stirring tank and mix evenly, then add 8kg of sawdust, 8kg of fly ash and 15kg of aluminum silicate fiber into the stirring tank, mix evenly to obtain slurry, pour the slurry into a mold with a non-woven fabric on the bottom, cover the surface with non-woven fabric after cast spreading, mold at 170°C and 4.5MPa for 25min, dry and demould, and sand and polish to obtain a prefabricated board.

[0031] S5: The deodorizing filler, color powder and melamine resin are stirred and mixed uniformly in a mass ratio of 5:2:90 to obtain resin slurry, the prefabricated board is immersed in the resin slurry for 5 minutes, transferred to a mold, molded at a temperature of 185° C. and a pressure of 3 MPa for 5 minutes, and demolded to obtain a nano deodorizing fireproof board.

[0032] Embodiment 2: A production process of a nano deodorizing fireproof board material, comprising the following steps:

[0033] S1: Add 100L of methyl orthosilicate, 12kg of polyethylene oxide and 245L of hydrochloric acid with a molar concentration of 0.01mol / L into a reactor, stir at 400r / min for 70min, then add 46.5L of propylene oxide into the reactor and continue stirring for 1.5min, let stand at 38°C for 69h, soak the formed gel in anhydrous ethanol for 5.5h, wash it twice, vacuum dry it, and grind it to obtain a porous carrier powder.

[0034] S2: Add 4kg of hydrated copper nitrate, 8.4kg of 2-methylimidazole and 750L of anhydrous methanol into the reactor, stir at 250r / min for 70min, then add 2.5kg of porous carrier powder into the reactor, ultrasonically disperse for 25min, let stand at 38°C for 24h, centrifuge and wash the filter cake with anhydrous methanol 4 times, transfer to a tubular furnace after vacuum drying, and keep warm for 2.8h at 810°C under a protective gas atmosphere. The protective gas is a mixture of argon and hydrogen in a volume ratio of 3:1 to obtain a nano deodorant powder.

[0035] S3: Add 1000L Tris-HCl buffer solution with a pH value of 8.5 and 5kg dopamine hydrochloride into the reactor, stir and mix, then add 2.3kg nano deodorant powder into the reactor, stir at 250r / min for 18min, ultrasonically disperse for 8min, then stir and react at 22°C for 13h, centrifuge and filter, and vacuum dry the filter cake to obtain a deodorant filler.

[0036] S4: Add 70kg of magnesium oxide powder, 25kg of anhydrous magnesium chloride powder, 12.5kg of glass fiber powder, 12.5kg of alumina powder, 0.8kg of hydroxymethyl cellulose and 6kg of water into a stirring tank and mix evenly, then add 10kg of sawdust, 10kg of fly ash and 18kg of aluminum silicate fiber into the stirring tank, mix evenly to obtain slurry, pour the slurry into a mold with a non-woven fabric on the bottom, cover the surface with non-woven fabric after casting and spreading, mold at 175°C and 4.8MPa for 28min, dry and demould, and sand and polish to obtain a prefabricated board.

[0037] S5: The deodorizing filler, color powder and melamine resin are stirred and mixed uniformly in a mass ratio of 6.5:3:92.5 to obtain resin slurry, the prefabricated board is immersed in the resin slurry for 8 minutes, transferred to a mold, molded at a temperature of 188°C and a pressure of 3.2MPa for 6.5 minutes, and demolded to obtain a nano deodorizing fireproof board.

[0038] Embodiment 3: A production process of a nano deodorizing fireproof board material, comprising the following steps:

[0039] S1: Add 100L of methyl orthosilicate, 12kg of polyethylene oxide and 250L of hydrochloric acid with a molar concentration of 0.01mol / L into a reactor, stir at 500r / min for 80min, then add 47L of propylene oxide into the reactor and continue stirring for 2min, let stand at 40°C for 72h, soak the formed gel in anhydrous ethanol for 6h, wash it 3 times, vacuum dry it, and crush it to obtain a porous carrier powder.

[0040] S2: Add 4kg of hydrated copper nitrate, 8.5kg of 2-methylimidazole and 800L of anhydrous methanol into the reactor, stir at 300r / min for 80min, then add 2.5kg of porous carrier powder into the reactor, ultrasonically disperse for 30min, let stand at 40°C for 24h, centrifuge and wash the filter cake with anhydrous methanol 5 times, transfer to a tubular furnace after vacuum drying, and keep warm for 3h at 820°C under a protective gas atmosphere. The protective gas is a mixture of argon and hydrogen in a volume ratio of 3:1 to obtain a nano deodorant powder.

[0041] S3: Add 1000L Tris-HCl buffer with a pH value of 8.5 and 5kg dopamine hydrochloride into the reactor, stir and mix, then add 2.4kg nano deodorant powder into the reactor, stir at 300r / min for 20min, ultrasonically disperse for 10min, then stir and react at 25°C for 14h, centrifuge and filter, and vacuum dry the filter cake to obtain a deodorant filler.

[0042] S4: Add 80kg of magnesium oxide powder, 30kg of anhydrous magnesium chloride powder, 15kg of glass fiber powder, 15kg of alumina powder, 1kg of hydroxymethyl cellulose and 7kg of water into a stirring tank and mix evenly, then add 12kg of sawdust, 12kg of fly ash and 20kg of aluminum silicate fiber into the stirring tank, mix evenly to obtain slurry, pour the slurry into a mold with a non-woven fabric on the bottom, cover the surface with non-woven fabric after cast spreading, mold at 180°C and 5MPa for 30min, dry and demould, and sand and polish to obtain a prefabricated board.

[0043] S5: The deodorizing filler, color powder and melamine resin are stirred and mixed uniformly in a mass ratio of 8:4:95 to obtain resin slurry, the prefabricated board is immersed in the resin slurry for 10 minutes, transferred to a mold, molded at a temperature of 190° C. and a pressure of 3.5 MPa for 8 minutes, and demolded to obtain a nano deodorizing fireproof board.

[0044] Comparative Example 1: Based on Example 3, the deodorizing filler prepared in step S3 is not added, and the other steps remain unchanged to prepare a fireproof board.

[0045] Comparative Example 2: On the basis of Example 3, the deodorizing filler in step S5 is replaced by the nano deodorizing powder in step S2, that is, the polydopamine coating treatment in step S3 is omitted, and the other steps remain unchanged to prepare a fireproof board.

[0046] The thickness of the fireproof board prepared in the embodiment and the comparative example is 18 mm. The melamine resin is melamine formaldehyde resin produced by Shandong Wangtong Chemical Co., Ltd., and the added color powder is commercially available iron red powder.

[0047] Performance tests were carried out on Examples 1 to 3 and Comparative Examples 1 to 2. Five closed containers made of transparent acrylic plates with a specification of 1m×1m×1m were prepared, and fireproof panels with different specifications of 10cm×10cm×18cm were placed in the closed containers. Odor was introduced into the closed containers, and the hydrogen sulfide content in the odor was controlled to be 30ppm and the ammonia concentration to be 70ppm in the initial state. The containers were allowed to stand under natural light for 30 minutes, and the concentrations of hydrogen sulfide and ammonia in the closed containers were tested again.

[0048] The results are shown in Table 1:

[0049] Table 1

[0050]

[0051] It can be seen from Table 1 that the fireproof panels in Examples 1 to 3 can reduce the concentrations of hydrogen sulfide and ammonia and have a good deodorizing effect.

[0052] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process of nano deodorizing fireproof board, characterized in that: The steps include: Step 1: adding magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, aluminum oxide powder, hydroxymethyl cellulose and clean water into a stirring tank and mixing them evenly, then adding sawdust, fly ash and aluminum silicate fiber into the stirring tank, mixing evenly to obtain a slurry; Step 2: pour the slurry into a mold with a non-woven fabric on the bottom, cover the non-woven fabric on the surface after casting and spreading, mold at a temperature of 170-180°C and a pressure of 4.5-5MPa for 25-30 minutes, dry and demould, and sand and polish to obtain a prefabricated board; Step 3: Stir and mix the deodorizing filler, color powder and melamine resin evenly to obtain resin slurry, immerse the prefabricated board in the resin slurry for 5-10 minutes, transfer it to the mold, mold it at a temperature of 185-190°C and a pressure of 3-3.5MPa for 5-8 minutes, and demold it to obtain the nano deodorizing fireproof board.

2. The production process of a nano deodorizing fireproof board according to claim 1, characterized in that: The mass ratio of the magnesium oxide powder, anhydrous magnesium chloride powder, glass fiber powder, aluminum oxide powder, hydroxymethyl cellulose, clean water, sawdust, fly ash and aluminum silicate fiber is 60-80: 20-30: 10-15: 10-15: 0.5-1: 5-7: 8-12: 8-12: 15-20.

3. The production process of a nano deodorizing fireproof board according to claim 1, characterized in that: The mass ratio of the deodorizing filler, the color powder and the melamine resin is 5-8:2-4:90-95.

4. The production process of a nano deodorizing fireproof board according to claim 1, characterized in that: The deodorizing filler is prepared by the following steps: Add Tris-HCl buffer with a pH value of 8.5 and dopamine hydrochloride into a reaction kettle, stir and mix, then add nano deodorant powder into the reaction kettle, stir at 200-300 r / min for 15-20 min, ultrasonically disperse for 5-10 min, then stir and react at 20-25° C. for 12-14 h, centrifuge and filter, and vacuum dry the filter cake to obtain a deodorant filler.

5. The production process of a nano deodorizing fireproof board according to claim 4, characterized in that: The usage ratio of the Tris-HCl buffer, dopamine hydrochloride and nano deodorant powder is 1000 mL: 5 g: 2.2-2.4 g.

6. The production process of a nano deodorizing fireproof board according to claim 1, characterized in that: The nano deodorant powder is prepared by the following steps: Add hydrated copper nitrate, 2-methylimidazole and anhydrous methanol into a reaction kettle, stir at 200-300 r / min for 60-80 min, then add porous carrier powder into the reaction kettle, ultrasonically disperse for 20-30 min, stand at 35-40° C. for 24 h, centrifuge and filter, wash the filter cake with anhydrous methanol for 3-5 times, transfer to a tube furnace after vacuum drying, and keep warm at 800-820° C. for 2.5-3 h in a protective gas atmosphere to obtain nano deodorant powder; The protective gas is a mixture of argon and hydrogen in a volume ratio of 3:

1.

7. The production process of a nano deodorizing fireproof board according to claim 6, characterized in that: The usage ratio of the hydrated copper nitrate, 2-methylimidazole, anhydrous methanol and porous carrier powder is 0.4g: 0.84-0.85g: 70-80mL: 0.25g.

8. The production process of a nano deodorizing fireproof board according to claim 6, characterized in that: The porous carrier powder is prepared by the following steps: Methyl orthosilicate, polyethylene oxide and hydrochloric acid with a molar concentration of 0.01 mol / L are added into a reactor, stirred at 300-500 r / min for 60-80 min, propylene oxide is added into the reactor and stirred for 1-2 min, and allowed to stand at 35-40° C. for 66-72 h. The formed gel is soaked in anhydrous ethanol for 5-6 h, washed 2-3 times, vacuum dried and crushed to obtain a porous carrier powder.

9. The production process of a nano deodorizing fireproof board according to claim 8, characterized in that: The dosage ratio of methyl orthosilicate, polyethylene oxide, 0.01 mol / L hydrochloric acid and propylene oxide is 1 mL: 0.12 g: 2.4-2.5 mL: 0.46-0.47 mL.

10. A nano deodorizing fireproof board, characterized in that: It is prepared by the production process described in any one of claims 1 to 9.